Are group assignments effective pedagogy or a waste of time? A review of the literature and implications for practice. Issue 3 (October 2020) - Thom, Michael
Group assignments are a near-universal feature of classrooms around the world. They are broadly viewed as more effective than passive forms of learning and are assumed to position students for success in fields that demand high levels of interpersonal communication, like public affairs. But does research support that view? This article examines the literature on group assignments. It illustrates that most studies on group assignments suffer from weak research designs, leaving little empirical basis for their presumed benefits. The article offers suggestions for improving the design and implementation of group assignments, but also encourages instructors to reconsider their use.